2021
DOI: 10.1016/j.ajic.2020.06.187
|View full text |Cite|
|
Sign up to set email alerts
|

An evaluation of cleaning practices at a teaching hospital

Abstract: Background: The COVID-19 outbreak has highlighted the role of hospital-acquired infections in spreading epidemics. Adequately cleaning surfaces in patient rooms is an essential part of this fight to reduce the spread. Traditional audits, however, are insufficient. This study assesses surface cleaning practices using ultravoilet (UV) marker technology and the extent to which this technology can help improve cleaning audits and practices. Methods: One hundred and forty-four audits (1,235 surfaces) were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
15
0
7
Order By: Relevance
“…Surface cleanliness has been a focus of research for several years, particularly in hospitals because of the potential spread of disease, and more recently in hotels (Al-Hamad and Maxwell, 2008; Calfee et al , 2020; Kline et al , 2014; Lei et al , 2019; Meyer et al , 2020; Otter and French, 2009; Park et al , 2019). In 2010, the Hospital Infection Control Practices Advisory Committee and the CDC put forth the recommendation to clean high-touch areas [defined as “frequently touched by hands” (Park et al , 2019)] more frequently than low-touch surfaces [defined as “not frequently touched by hands” (Park et al , 2019)] (Huslage et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface cleanliness has been a focus of research for several years, particularly in hospitals because of the potential spread of disease, and more recently in hotels (Al-Hamad and Maxwell, 2008; Calfee et al , 2020; Kline et al , 2014; Lei et al , 2019; Meyer et al , 2020; Otter and French, 2009; Park et al , 2019). In 2010, the Hospital Infection Control Practices Advisory Committee and the CDC put forth the recommendation to clean high-touch areas [defined as “frequently touched by hands” (Park et al , 2019)] more frequently than low-touch surfaces [defined as “not frequently touched by hands” (Park et al , 2019)] (Huslage et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Huslage et al (2010) found that contaminated hospital surfaces, contaminated equipment and contaminated hands were all linked to pathogen transmission and led to multiple outbreaks of infection. More recently, Meyer et al (2020) reiterated the need to clean high-touch surfaces in hospitals compared to other surfaces. High- and low-touch areas have also been a focus of research in hotels where high-touch surfaces in the guestroom were first identified and then tested to see if the surfaces were actually cleaned properly and met guests’ expectations (Park et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental cleanliness is a foundational concept in nursing and midwifery 11 , but one that may be undervalued or brushed aside due to time constraints, lack of resources, and other factors 3 , 4 , 5 , 12 , 13 . As shown in this study, workplace factors can play a key role in shaping compliance with IPC policies.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental cleaning is key to preventing infections in healthcare and is cost-effective 1 , 2 . Workplace factors such as time pressures, staff knowledge, work processes, organisational structures, and the everyday complexity of health care systems can play a key role in how well environmental cleanliness is maintained and healthcare associated infections (HCAIs) prevented 3 , 4 , 5 , 6 . This paper builds on previous work from the authors, 7 which explored nurses’ and midwives’ knowledge of infection prevention and control (IPC) and cleaning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Además, en lo que respecta al etiquetado de los envases de los desinfectantes, estos no tienen identificación, ni fecha de activación o preparación del desinfectante, en un 25% que el hospital de segundo nivel, situación similar ocurre en el hospital de tercer nivel con un 34%. Para garantizar la calidad de los desinfectantes estos durante el tiempo de almacenamiento, deben permanecer sellados, si se debe efectuar preparaciones este debe ser en volumen pequeño, considerando las especificaciones del fabricante para uso único y diario (27,28).…”
Section: Discussionunclassified